The Man with a Dream and a Plan: Xi Jinping, the “Chinese Dream” and the Belt and Road Initiative - Musabelliu, Marsela (Power Shifts in East Asia and Their Implications for Asia–Europe Relations, 2019)
The purpose of this paper is to seek the organizing principle of China’s Belt and Road Initiative in terms of the People’s Republic of China’s overall foreign policy objectives, and, in order to do this, an understanding of the leadership of the Middle Kingdom becomes imperative. There are five generations of Chinese leaders since the proclamation of the PRC and obviously each of them has had distinct attitudes when it comes to foreign policy and the decision making process, since their actions have been the outcome of specific historical, social and geopolitical conditions. Notwithstanding, we see a continuity of grand strategies and application of the same principles of Socialism with Chinese Characteristics, inherited from one establishment by the other. The current leader Xi Jinping, soon after getting to be General Secretary of the Communist Party in late 2012, expressed what might turn into the hallmark of his administration: “The Chinese Dream – the great rejuvenation of the Chinese nation.” Some months later the New Silk Road Strategy was proclaimed; the proposed revival of a great trade route which, two thousand years ago, bridged Eastern and Western cultures across the Eurasian continent, becomes in the 21st century the fulcrum of the Belt and Road Initiative and the blueprint of the actual Chinese foreign policy.